Far infrared light irradiation enhances Aβ clearance via increased exocytotic microglial ATP and ameliorates cognitive deficit in Alzheimer’s disease-like mice - Qingyong Li; Jun Peng; Yuelian Luo; Jiaxin Zhou; Tailin Li; Lin Cao; Shuling Peng; Zhiyi Zuo; Zhi Wang (Journal of Neuroinflammation, 2022)
Abstract Background Exposure to sunlight may decrease the risk of developing Alzheimer’s disease (AD), and visible and near infrared light have been proposed as a possible therapeutic strategy for AD. Here, we investigated the effects of the visible, near infrared and far infrared (FIR) light on the cognitive ability of AD mice, and found that FIR light also showed potential in the improvement of cognitive dysfunction in AD. However, the related mechanism remains to be elucidated. Methods Morris water maze was used to evaluate the cognitive ability of APPswe/PSEN1dE9 double-transgenic AD mice after light treatment. Western blot was carried out to detect the expression of protein involved in synaptic function and amyloid-β (Aβ) production. The protein amount of interleukin (IL)-1β, IL-6, Aβ1-40 and Aβ1-42 were determined using enzyme-linked immunosorbent assay. The mRNA level of receptors was performed using real-time quantitative polymerase chain reaction. Immunostaining was performed to characterize the Aβ burden and microglial Aβ phagocytosis in the brain of AD mice. The Aβ phagocytosis of primary cultured microglia and BV2 were assessed by flow cytometry. The energy metabolism changes were evaluated using related assay kits, including adenosine triphosphate (ATP), lactate content, mitochondrial respiratory chain complex enzymatic activity and oxidized/reduced nicotinamide adenine dinucleotide assay kits. Results Our results showed that FIR light reduced Aβ burden, a hallmark of AD neuropathology, alleviated neuroinflammation, restored the expression of the presynaptic protein synaptophysin, and ameliorated learning and memory impairment in the AD mice. FIR light enhanced mitochondrial oxidative phosphorylation pathway to increase ATP production. This increased intracellular ATP promoted the extracellular ATP release from microglia stimulated by Aβ, leading to the enhanced Aβ phagocytosis through phosphoinositide 3-kinase/mammalian target of rapamycin pathways for Aβ clearance. Conclusions Our findings have uncovered a previously unappreciated function of FIR light in inducing microglial phagocytosis to clean Aβ, which may be the mechanisms for FIR light to improve cognitive dysfunction in AD mice. These results suggest that FIR light treatment is a potential therapeutic strategy for AD.